Hyperactivity and attention disorders of childhood - Sandberg, Seija (Cambridge child and adolescent psychiatry series., 2002)
This new edition is thoroughly revised and updated. Some chapters are completely new, and some of the areas dealt with in the first edition are being covered by new authors. This will be essential reading for all professionals involved in the management and care of people with ADHD.